A study of the role of Shiite symbols in the spatial sense of the holy places of the Safavid period A case study of Imam Mosque and Sheikh Lotfollah Mosque - Reza Oryaninezhad; Omid Dezhdar; Mohammad Mehdi Soroush (هنر اسلامی, 2022)
In organizing the mosques of the Safavid period in Isfahan, one can find principles that have been the decision-making infrastructure of the designers of this period for designing designs and decorations. It is a combination of nest-to-nest quality in quantity, which in the qualitative stage uses two separate techniques for identification and communication, which include Delphi and coding, and in the quantitative part with inferential statistical tests. There are space users in these mosques, which due to lack of accurate information has been calculated using Morgan table, which 384 people are selected to select the highest number. The results of interviews with those experts were analyzed with ATLASTI software and in a quantitative part with inferential statistical tests and using SPSS software, the factor share of each symptom was examined. Findings show that the highest factor share is related to the formation of large and small spaces, which include the altar, basin, nave, courtyard of the mosque, dome, with a value of (1,000) and the lowest factor share. To architectural materials with a value of (0.523). The arrangement of spaces in mosques in the Safavid period, especially the mosques of Sheikh Lotfollah and Imam, has caused the idea of ​​a calm and beautiful space to be formed and a rich and wonderful combination has been invented.